Recurrent intrahepatic obstructive jaundice: report of a case - Zileli, M. Şeref; Çoruh, Mithat (The Turkish Journal of Pediatrics, 1962)
A ten year old girl with recurrent intrahepatic obstructive jaundice is reported. A variant of the infectious hepatitis virus is believed to be responsible for the recurrent course.We acknowledge with gratitude the interpretations made of our liver biopsy slides by Dr. I. N. Dubin, Dr. W. H. J. Summerskill and Dr. A. Günalp.